PERAN BRAND IMAGE MEMEDIASI PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN SENSATIA BOTANICALS DI DENPASAR - Ni Made Sinta Erisma Dewi; i Gusti Ayu Ketut Giantari (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
Public concerns about environmental problems encourage changes in consumer behavior. People are becoming more selective in choosing the products to be consumed in order to minimize the negative effects on the environment. Including in choosing skincare with environmentally friendly ingredients. This studied aim to explain the roles of branding images mediating an influences of the green markering in the purchasing descision on Sensatia Botanicals at Denpasar City. The research was conducting using 100 respondents taken using purposive sampling. Data analyse technique uses Path Analyze which is an equipped with a Sobel Test to test on role of mediation. The results showed that 1) Green marketing had a positive and significant influence on the purchasing decision of Sensatia Botanicals in Denpasar City, 2) Green marketing has a positif and significants impact on brand images at Denpasar City, 3) Brand image had a positive and significant impact on decisions. purchase of Sensatia Botanicals at Denpasar City, 4) Brand Images is positively and significantly able to mediate an effect of green marketing on the purchassing decision of Sensatia Botanicals in Denpasar City. The implications of Sensatia Botanicals' research results are expected to be able to consistently maintain a green marketing and maintain brand image to increase sales.